The Oxford handbook of science and medicine in the classical world - Keyser, Paul T.; Scarborough, John (Oxford University Press, 2018)
Ancient scientific traditions beyond Greece and Rome -- Early Greek science -- Hellenistic Greek science -- Greco-Roman science -- Late antique and early Byzantine science
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte Anfänge-650; Medizin; Naturwissenschaften; Römisches Reich; Griechenland